2013
DOI: 10.1007/s10935-013-0295-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Initial Uptake of Human Papillomavirus Vaccine Uptake Among Rural Appalachian Young Women

Abstract: Women in Appalachian Kentucky experience a high burden of cervical cancer and have low rates of human papillomavirus (HPV) vaccination. The purpose of this study was to identify normative influences predicting initial HPV vaccine uptake among a sample of young women in southeastern Kentucky. Women (N = 495), ages 18 through 26 years, were recruited from clinics and community colleges. After completing a questionnaire, women received a free voucher for HPV vaccination. Whether women redeemed the voucher for Dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…Three of the 29 articles were companion reports 21 23 of two primary publications. 15 , 16 We report on the 26 primary publications ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three of the 29 articles were companion reports 21 23 of two primary publications. 15 , 16 We report on the 26 primary publications ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen articles reported the results of randomized controlled trials, 14 , 16 , 17 , 19 , 24 33 two reported the results of controlled clinical trials, 34 , 35 one reported the results of a crossover clinical trial, 36 two reported the results of cohort studies, 6 , 37 and seven reported the results of uncontrolled before–after studies. 15 , 38 43 Eleven of the 26 trials described the effects of behavioral interventions when conducted along with cointerventions, including motivational enhancement therapy, 14 , 16 , 26 , 28 , 33 relaxation-control treatment, 14 cognitive behavioral therapy, 16 , 31 , 38 drug counseling, 16 multidisciplinary adherence support, 39 motivational interviewing, 39 and instructional materials or information. 32 , 40 , 41…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Two vaccines (HPV4, Gardasil R ; HPV2, Cervarix R ) are now widely available for the primary prevention of HPV infection and cervical cancer. 2 The Centers for Disease Control and Prevention (CDC) recommends routine HPV vaccination for females ages 11-12 and catch-up vaccination for females ages [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Current CDC guidelines recommend that the second dose of the HPV vaccine series be administed 1-2 months after the first injection; the third dose is administered 6 months after the first dose.…”
mentioning
confidence: 99%
“…Other noted barriers to HPV vaccination among Appalachian women include lack of transportation, limited parental/peer/health care provider support, cultural views, and lack of knowledge regarding cervical cancer prevention and HPV. 13,[15][16][17] There is an additional barrier to preventive cancer behavior, however, that has received limited attention as it relates to HPV vaccination, and that is the concept of fatalism. Fatalism has been examined as a potential determinant for engaging in preventive cancer strategies, including cancer information seeking, screening (eg, colorectal cancer screening, Papanicolaou [Pap] testing, mammography) and preventive behaviors (eg, diet, exercise, smoking).…”
mentioning
confidence: 99%